Cohesive devices in English Information technology reading texts and implications in teaching and learning English for specific purposes at The People’s Police University of Technology and Logistics / Trần Thị Vân Anh; GVHD: Hồ Ngọc Trung - Trần, Thị Vân Anh
The thesis aims at finding out the solutions to improve students’ capability in using English cohesive devices in English for Information and Technology at The People’s Police University of Technology and Logistics (PPUTL). From this aim, the study attempts to analyze cohesive devices in English IT reading texts in terms of type and number of occurrence; to find out the common mistakes made by students via the survey test and suggest some solutions to improve students’ capabilities in using cohesive devices effectively. In order to carry out this study, the descriptive, quantitative and qualitative methods are used. The most prominent finding is that lexical cohesive devices are used more often than grammatical one. The statistics shows that there are 412 items (52,03%) of lexical cohesive devices and 365 items (46,97%) of grammatical cohesive devices. In addition to that, from the findings of the test and personal observation, the researcher has found out some common mistakes in using cohesive devices made by PPUTL students. The most significant outcome of the study is that it gives an awareness of students’ difficulties in learning and translating cohesive devices in IT texts. Hence, it benefits both teachers and students